Criteria of existence of one- and two-layer compounds (MeII, Ln)n+1BnO3n+1 - Titov, Y.A.; Slobodyanik, M.S.; Polubinskii, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
On the basis of the analysis and the generalization of data on the synthesized by the authors and known (MeII, Ln)n+1BnO3n+1-type compounds with layered perovskite-like structure (LPS), the necessary conditions of existence of compounds and phases compositions (MeII, Ln)n+1BIIInO3n+1 and (MeII, Ln)n+1(BIII,BIV)nO3n+1 (n = 1 and 2) with LPS are determined. They account for the ratio of the size of atoms and the ionicity of bonds A — O and B — O in crystals and substantially simplify the directed search for new layered perovskite-like compounds and (MeII, Ln)n+1BnO3n+1-type phases.